Interrupt or reinforce? The impact of timeout on momentum in basketball game - Qiu, M.; Zhang, K.; Chao, Y.; Zhang, M. (Frontiers in Psychology, 2025)
Introduction: Timeouts are often viewed by coaches as an important means of intervening in a game, but their impact on the game`s momentum still lacks empirical research. This study aims to evaluate the impact of timeouts on momentum, defined as excellent offensive and defensive performance over a short period in basketball games, and to analyze the moderating role of contextual factors.